Characterization of a canine model of glycogen storage disease type IIIa - Haiqing Yi; Beth L. Thurberg; Sarah Curtis; Stephanie Austin; John Fyfe; Dwight D. Koeberl; Priya S. Kishnani; Baodong Sun (The Company of Biologists, 2012)
SUMMARY Glycogen storage disease type IIIa (GSD IIIa) is an autosomal recessive disease caused by deficiency of glycogen debranching enzyme (GDE) in liver and muscle. The disorder is clinically heterogeneous and progressive, and there is no effective treatment. Previously, a naturally occurring dog model for this condition was identified in curly-coated retrievers (CCR). The affected dogs carry a frame-shift mutation in the GDE gene and have no detectable GDE activity in liver and muscle. We characterized in detail the disease expression and progression in eight dogs from age 2 to 16 months. Monthly blood biochemistry revealed elevated and gradually increasing serum alanine transaminase (ALT), aspartate transaminase (AST) and alkaline phosphatase (ALP) activities; serum creatine phosphokinase (CPK) activity exceeded normal range after 12 months. Analysis of tissue biopsy specimens at 4, 12 and 16 months revealed abnormally high glycogen contents in liver and muscle of all dogs. Fasting liver glycogen content increased from 4 months to 12 months, but dropped at 16 months possibly caused by extended fibrosis; muscle glycogen content continually increased with age. Light microscopy revealed significant glycogen accumulation in hepatocytes at all ages. Liver histology showed progressive, age-related fibrosis. In muscle, scattered cytoplasmic glycogen deposits were present in most cells at 4 months, but large, lake-like accumulation developed by 12 and 16 months. Disruption of the contractile apparatus and fraying of myofibrils was observed in muscle at 12 and 16 months by electron microscopy. In conclusion, the CCR dogs are an accurate model of GSD IIIa that will improve our understanding of the disease progression and allow opportunities to investigate treatment interventions.